Intertextuality and Hosea 3: Did Hosea Purchase the Unnamed Woman to Enslave or Free Her? - Ahn, John J. (Journal of black religious thought, 2025)
Applying intertextuality, this article addresses the central problem in Hosea 3. That is, the purchase of the unnamed woman for fifteen shekels, a homer of barley, and a measure of wine, which equates to another fifteen shekels. Strangely, there is no ethical or moral consciousness on the purchasing of another human being by a prophet of God. Commentators have not paid enough attention to this troubling fact. In addition, scholars have inquired if the mythopoetic construction of reality of Hosea, a literary character, overshadows the fact that he may have been an actual prophet enacting troubling behavior. Sign acts are almost always troubling, making a theological point. The fact that the canonical editor(s) of the Book of Twelve may or may not be fully unaware of human trafficking is a modern critique.